2011
DOI: 10.1590/s0100-69162011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade econômica do sistema de adubação diferenciado comparado ao sistema de adubação convencional em lavoura cafeeira: um estudo de caso

Abstract: RESUMO:A agricultura de precisão surge como uma importante ferramenta para maximizar o gerenciamento da atividade cafeeira, principalmente para esta cultura, que possui elevado custo de produção. O presente trabalho teve por objetivo fazer um estudo comparativo da viabilidade econômica de dois sistemas de adubação na lavoura cafeeira: o sistema utilizando as técnicas da agricultura de precisão e o sistema de aplicação convencional. Os dados utilizados foram extraídos dos custos de produção da fazenda Brejão, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
3
0
5
Order By: Relevance
“…The result of the variables P, K, T, m and OM is similar to that found by Silva & Lima (2012). The result of the variables plant height and yield is similar to that reported by Carvalho et al (2013), and the yield was also similar to that found by Fonseca et al (2015).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The result of the variables P, K, T, m and OM is similar to that found by Silva & Lima (2012). The result of the variables plant height and yield is similar to that reported by Carvalho et al (2013), and the yield was also similar to that found by Fonseca et al (2015).…”
Section: Resultssupporting
confidence: 89%
“…Based on Precision Agriculture, the management imposed on the area in the seasons of 2007/2008 and 2008/2009 was differentiated fertilization, as described by Ferraz et al (2011); in the other seasons, fertilization was performed in the conventional way.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al (2008) encontraram, estudando diferentes tipos de amostragem para geração de dados de recomendação de correção de fertilidade em café, zonas de déficit e excesso de adubação e calagem na área quando utilizaram amostras georreferenciadas e geoestatística e ressaltaram a impossibilidade de se encontrar essas diferentes zonas utilizando-se do método aleatório de amostragem (ziguezague). Ferraz et al (2011) verificaram, comparando a adubação feita com base em agricultura de precisão com a adubação feita com base no método convencional, a viabilidade econômica do primeiro em lavouras de café, principalmente em grandes áreas.…”
Section: Resultsunclassified
“…Molin et al (2010), in a study comparing applications at variable and fixed rates in the coffee crop, observed that the area where the fertilizers were applied in variable rates showed a 34% yield increase, in comparison to the area under the application of fixed rates. Ferraz et al (2011) observed that manual application of variable rates of phosphorus and potassium was economically more advantageous, in comparison to the conventional application system.…”
Section: Introductionmentioning
confidence: 99%